The impact of temperature and skeletal muscle oxygen saturation on 40 km cycling time trial performance of male cyclists - S. H. Faulkner; P. Jobling; N. Wilson; R. James; E. Martin; K. Griggs (Physiological Reports)
Abstract Endurance performance declines in non‐heat‐acclimated athletes in warm conditions. Early studies did not use relevant wind speeds, increasing heat storage, and performance decline. Furthermore, deep hip flexion postures adopted in time‐trials (TTs) may limit skeletal muscle oxygenation (SmO2), compounding problems associated with heat storage in warm‐hot environments. The aim of this study was to employ an ecologically valid method of simulating TTs, using wind speeds closely replicating those in the real world (~40 km h−1). A secondary aim was to investigate how SmO2 was impacted by environmental conditions. Ten well‐trained cyclists volunteered for the study. They completed 3 simulated 40 km TT's in 10, 20, and 30 and 50% relative humidity. TT time was slower in 30°C (3666 ± 172 s) versus 10°C (3531 ± 144 s; p = 0.0029) and 20°C (3528 ± 160 s; p = 0.0033). Mean Tsk was highest in 30°C (34.4 ± 0.1°C) versus 10°C (25.4 ± 1.5°C) and 20°C (30.6 ± 0.3°C; all p < 0.0001). Larger ∆SmO2 was evident at 10°C (−1.3 ± 0.7%) and 20°C (−1.2 ± 0.7%) versus 30°C (0.4 ± 0.7%; both p < 0.0001). ∆SmO2 was correlated to ∆heart rate (r = −0.556, p < 0.0001) and power (r = −0.425, p < 0.0001). These data show that simulated TT performance is impaired >20°C.